An improved SAO network-based method for technology trend analysis: A case study of graphene. Issue 1 (February 2018) - Yang, Chao; Huang, Cui; Su, Jun
Highlights: Improved Subject-Action-Object (SAO) network-based method for analyzing trends in technology development. Constructing an SAO network based on SAO links. Calculating the strength of the relationship between Subject and Object. Identifying technology trends based on structural holes, changes in degree distribution, and shifts in network centrality. Abstract: This paper proposes an improved Subject-Action-Object (SAO) network-based method for analyzing trends in technology development. It attempts to address shortcomings of the traditional SAO network approach, i.e., when setting Subject, Action and Object as nodes of the network, there may be errors in explaining the relationship between Subject Node and Object Node, and the strength of the relationship between subject and object also cannot be identified. The proposed improved SAO network-based method in this paper includes: (1) a new method for constructing an SAO network based on SAO links that calculate the intensity of the relationship between nodes; (2) a model for identifying technology development trends based on structural holes, changes in the distribution of node degrees, and shifts in network centrality. An empirical study on graphene technology is used to illustrate the validity and feasibility of the proposed method.